Ma2aPracLectures 16-18

Ma2aPracLectures 16-18 - Lecture 16 For any m m-matrix M =...

Info iconThis preview shows pages 1–5. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Lecture 16 For any m m-matrix M = ( m ij ) , 1 i, j m, the exponential of M is defined by exp( M ) = e M = n =0 M n n ! , when the right hand side converges, with M = I . Notation: n =0 ( a n b n c n d n ) = n =0 a n n =0 b n n =0 c n n =0 d n Why is this relevant for us? Reason : If we have x = A x , where x = x 1 . . . x m , x = d x dt = dx 1 dt . . . dx m dt , and A an m m-matrix with constant coecients, a basic set of solutions is given by the columns of the matrix ( t ) = e At Note : ( t ) = Ae At = A ( t ). A set of basic solutions are given by the columns of ( t ) = ( x (1) x (2) . . . x ( m ) ) , with x ( i ) ( t ) = x ( i ) 1 ( t ) x ( i ) 2 ( t ) . . . x ( i ) m ( t ) , i m. We have mostly looked so far at the case where A has distinct eigenvalues. A modification is necessary for repeated eigenvalues ! Now we will look at the exponential of some simple 2 2-cases: 1 (i) A is diagonal : A = ( 1 2 ) A 2 = ( 2 1 2 1 ) , . . . , A n = ( n 1 n 2 ) So e A = A + A 1 1! + A 2 2! + + A n n ! + . . . = ( 1 0 0 1 ) + ( 1 2 ) + ( 2 2! 2 2 2! ) + + ( n 1 n ! n 2 n ! ) + . . . = ( 1 + 1 + 2 1 2! + + n n n ! 1 + 2 + 2 2 n ! + + n 2 n ! + . . . ) = ( e 1 e 2 ) Conclusion : exp ( 1 2 ) = ( e 1 e 2 ) Note : exp ( a b c d ) = ( e a e b e c e d ) ! (ii) A : upper triangular A = ( 1 0 1 ) A 2 = ( 1 2 1 ) A 3 = ( 1 3 1 ) , . . . , A n = ( 1 n 1 ) (by induction) Thus e A = n =0 A n n ! = n =0 ( 1 n ! n n ! 1 n ! ) = n =0 1 n ! n =0 n n ! n =0 1 n ! 2 n =0 1 n ! = e n =1 n n ! = n =1 1 ( n 1)! = k =0 1 k ! = e = e A = ( e e e ) Check : For A = ( 1 0 1 ) , e At = ( e t e t e t ) . (iii) A = ( 1 ) A 2 = ( 2 2 2 ) A 3 = ( 3 3 2 3 ) . . . A n = ( n n n 1 n ) Remembering that A = I , e A = n =0 n n ! n =0 n n 1 n ! n =0 n n ! Note that for any t , n =0 n n 1 t n n ! = n =1 n 1 t n ( n 1)! = t k =0 k t k k ! = te t Putting t = 1, e A = ( e e e ) Check : For A = ( 1 ) , e At = ( e t te t e t ) . 3 It appears hopeless to get a nice expression for e M for an arbitrary m m matrix M = ( m ij ), even for m = 2. We tackle this problem by appealing to similarity of matrices (also called conjugacy )....
View Full Document

Page1 / 15

Ma2aPracLectures 16-18 - Lecture 16 For any m m-matrix M =...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online